FOAMED POROUS HEAT-INSULATING MATERIALS ON THE BASIS OF ALUMINUM - V. A. Kalinichenko; A. A. Andrushevich (Литьë и металлургия, 2012)
The article deals with methods for the production of metallic materials with porous structure during crystallization depending on the used foundry technologies. It is shown that by using modern scientific and technological advances it has possible to improve the traditional methods and the development of new casting processes, providing production of cast parts with different porous structure and special properties.